2017
DOI: 10.1186/s13104-017-2866-4
|View full text |Cite
|
Sign up to set email alerts
|

First case report of Providencia Rettgeri neonatal sepsis

Abstract: BackgroundProvidencia are gram negative motile rods and is a member of the Enterobacteriaceae family. It consists of five species, namely Providencia alcalifaciens, Providencia rustigianii, Providencia stuartii, Providencia rettgeri and Providencia heimbachae. These are opportunistic pathogens and leads to infections in immunocompromised host. Providencia rettgeri has been associated with the nosocomial infections of the urinary tract and infections of wounds, burns and blood. Providencia rettgeri is very rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…pneumoniae , and P. rettgeri are usually isolated from specimens in the routine clinical microbiology laboratories. Most of them have been identified as opportunistic pathogens that are commonly responsible for urinary tract infection (UTI) (Sharma et al, 2017[ 19 ]; Wagenlehner et al, 2014[ 20 ]). The most causative pathogen of UTI has been reported such as E. coli and occasionally K. pneumoniae (Wagenlehner et al, 2014[ 20 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pneumoniae , and P. rettgeri are usually isolated from specimens in the routine clinical microbiology laboratories. Most of them have been identified as opportunistic pathogens that are commonly responsible for urinary tract infection (UTI) (Sharma et al, 2017[ 19 ]; Wagenlehner et al, 2014[ 20 ]). The most causative pathogen of UTI has been reported such as E. coli and occasionally K. pneumoniae (Wagenlehner et al, 2014[ 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae also causes severe pneumonia, upper respiratory tract infection, wound infection, meningitis, and septicemia (Khan et al, 2015[ 12 ]). P. rettgeri has been partly reported as a causative pathogen of neonatal sepsis (Sharma et al, 2017[ 19 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have revealed pH tolerance of this species ranging from 4.5 to 9/10 (Claudia et al, 1999;Janda and Abbott, 2010;Igbinosa et al, 2012) with an optimum of 7.5. Likewise, an optimum pH range (6-8) for Providencia species, pH 6-9 for Raoultella ornithinolytica, pH 5-9 for Alcaligenes sp, pH 5-7.1 for Klebsiella pneumoniae and pH 5-10 for Pseudomonas sp (Bruce et al, 1981;Naqvi, 2007;Hossain et al, 2016;Lu et al, 2017;Sharma et al, 2017;Aleanizy et al, 2018) have been recorded. This study has however shown a higher tolerance of these isolates at different culture conditions but also concurrent with the reported optimum ranges.…”
Section: Discussionmentioning
confidence: 94%
“…Providencia rettgeri was first reported by Rettger (1909) from a cholera-like epidemic in chickens and further characterized in F I G U R E 2 Neighbor-joining phylogenetic tree obtained from the analysis of the 16S rDNA nucleotide sequences from this study (MN006176 and MN006177), and sequences obtained from GenBank. The Numbers on each node are the bootstrap values for 1,000 replicates 1918 (Sharma et al, 2017;Tu, Tu, Tung, Hieu, & Romero-Jovel, 2014). The bacteria is known to interact with a variety of organisms, including loggerhead sea turtles, humans, insects (Galac & Lazzaro, 2011;Hokama et al, 2005;Mohamedova, Valcheva, Draganova, Naydenov, & Borisov, 2017;Sharma et al, 2017), nematodes (Jackson et al, 1995), frogs (Penner & Hennessy, 1979) and…”
Section: Discussionmentioning
confidence: 99%